Digital Transformation and Inclusive Growth in Developing Economies: Lessons from Burundi and Haiti - Jean-Baptiste Innocent Nyangoma; Frantz Jacques Louis; Rakesh Kumar Sharma (Journal GoodWill, 2025)
This study explores the nexus between digital transformation and inclusive growth in developing economies, with a specific focus on Burundi and Haiti. The research aims to analyze how digital innovation fosters economic inclusion, institutional strengthening, and sustainable development in fragile contexts. Employing a mixed-method approach that integrates secondary data analysis, policy document review, and semi-structured expert interviews, the study investigates the socio-economic implications of digitalization in key sectors, including finance, education, and governance. The findings reveal that digital transformation significantly contributes to inclusive economic growth by promoting access to financial services, supporting entrepreneurship, and enhancing public service delivery. However, these benefits remain unevenly distributed due to challenges such as inadequate ICT infrastructure, governance weaknesses, and low levels of digital literacy. In Burundi, connectivity gaps limit rural participation in the digital economy, while in Haiti, political instability and institutional fragmentation hinder the long-term sustainability of digital initiatives. The study concludes that digital transformation can serve as a catalyst for inclusive development when accompanied by strong institutional frameworks, targeted investments in digital infrastructure, and comprehensive capacity-building programs. This research enriches the academic discourse on digital inclusion in low-income economies and provides actionable insights for policymakers seeking to integrate digital strategies into equitable growth agendas.